Role of interactions in pharmacogenetic studies: leukotrienes in asthma. (June 2013) - Via, Marc; Tcheurekdjian, Haig; González Burchard, Esteban
Researchers have identified thousands of loci involved in complex traits and drug response. However, in most cases they only explain a small proportion of the heritability of the trait. Among different strategies conducted to identify this 'missing heritability', here we illustrate the importance of complex gene–environment interactions using findings regarding the role of leukotrienes on the bronchodilator response to albuterol in Latino asthmatics. Patients managing their asthma with leukotriene-modifying medication presented higher increases in the bronchodilator response to albuterol. Moreover, interactions between genes responsible for leukotriene production were associated with a decreased risk of asthma. Combining genetic and pharmacologic effects, leukotriene-modifying users carrying certain combinations of alleles presented higher improvements in lung function after bronchodilator administration. Genes and drugs act at different orders of interaction (from individual effects to gene–gene–drug–drug interactions) and population-specific effects have to be considered. These results may be extrapolated to other complex phenotypes.